Comprehensive multidimensional gas chromatography for the analysis of Fischer-Tropsch products - Van der Westhuizen, Katriena Elizabet (Stellenbosch : Stellenbosch University, 2011)
Thesis (PhD)--University of Stellenbosch, 2011.